2017
DOI: 10.3390/e19080423
|View full text |Cite
|
Sign up to set email alerts
|

An Improved System for Utilizing Low-Temperature Waste Heat of Flue Gas from Coal-Fired Power Plants

Abstract: Abstract:In this paper, an improved system to efficiently utilize the low-temperature waste heat from the flue gas of coal-fired power plants is proposed based on heat cascade theory. The essence of the proposed system is that the waste heat of exhausted flue gas is not only used to preheat air for assisting coal combustion as usual but also to heat up feedwater and for low-pressure steam extraction. Air preheating is performed by both the exhaust flue gas in the boiler island and the low-pressure steam extrac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Recent papers [1][2][3][4] prove that this topic is a well-studied one by the analysis of thermodynamic models for the simulation and optimization of power systems [1,2], as well as energy and exergy analysis of waste heat recovery systems [3,4]. For instance, an assessment with the citation indexing service Web of Science, that provides a comprehensive citation search through multiple databases, gives for "waste heat" a total of 23,717 references within its core collection over the period 1950-2017, of which 313 are highly cited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent papers [1][2][3][4] prove that this topic is a well-studied one by the analysis of thermodynamic models for the simulation and optimization of power systems [1,2], as well as energy and exergy analysis of waste heat recovery systems [3,4]. For instance, an assessment with the citation indexing service Web of Science, that provides a comprehensive citation search through multiple databases, gives for "waste heat" a total of 23,717 references within its core collection over the period 1950-2017, of which 313 are highly cited.…”
Section: Introductionmentioning
confidence: 99%
“…The paper topic is mainly concerned by fundamental aspects and methodology than by aspects developed regarding process sites, even if these developments become more and more explored [2,3,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [9] suggested use two-stage air preheater and LTE to heat condensed water and inlet air, which saved more high-grade extraction steam for power generation. Huang et al [10] proposed an improved waste heat use system for power plant boilers based on the traditional bypass flue heat recovery system, in which low-pressure steam is extracted from the low-pressure cylinder to preheat the air, replacing high-temperature flue gas to heat the feed water of the boiler, and the calculation showed the unit's exergy efficiency was increased to 45.46% on a 1000 MW unit. Liu et al [11] introduced a coupled high-low energy grade flus gas waste heat recovery system (CWHRS) applied to a 1000 MW double-reheat unit, which has produced good energy-saving effects.…”
Section: Introductionmentioning
confidence: 99%
“…An Improved System for utilizing low-temperature waste heat of flue gas from coal-fired power plants was carried out by Huang et al [8]. In this research article, an improved system to efficiently utilize the low-temperature waste heat from the flue gas of coal-fired power plants was proposed based on heat cascade theory.…”
mentioning
confidence: 99%